More than a curriculum : education for peace and development - Galtung, Johan; Udayakumar, S. P. (Emerald Publishing Limited : Information Age Publishing Inc., 2013)
Exploring the field of peace education, the bulk of the book analyzes and critically evaluates contemporary schools and universities. Providing some successful and not-so-successful alternative school and university projects and experiments, the book proposes peace and development education as a life process and presents a whole array of non-conventional tools and approaches.The unique feature of the book is that instead of putting emphasis on teaching peace and development, it insists on being and becoming what we teach. It makes a great textbook for education courses and programs, and a good handbook for peace educators and peace researchers around the world.The authors of the book are two teachers who are not attached to any regular educational institution anywhere in the world and are qualified to say what they have said in the book. The two authors have played significant, instrumental roles in promoting peace studies.
Keywords: International education.; Education -- Aims and objectives.; Peace -- Study and teaching.; Economic development -- Effect of education on.; Education -- Aims & Objectives.; Moral and social purpose of education.; Educational strategies and policy.; elektronické knihy; electronic books